Die Anwendbarkeit fremden Kartellrechts Eine Untersuchung des europäischen und US-amerikanischen Kollisionsrechts für private Kartellschadensersatzklagen im Zivilverfahren - Olbing, Jakob (Mohr Siebeck, 2025)
International antitrust violations pose a challenge in civil antitrust damages litigation. Damages incurred abroad are difficult to assess and compensate. Jakob Olbing examines the extent to which competent German and American courts can and should apply foreign antitrust law to address this challenge.
PublicationDate: 20250429
Keywords: Internationale Zuständigkeit -- IPR -- private enforcement -- Conflict of Laws -- internationale Kartelle -- Parallele Verfahren -- Bürgerliches Recht -- Handels- und Gesellschaftsrecht, Wirtschaftsrecht, Steuerrecht -- Internationales Privatrecht -- Zivilverfahrensrecht, Insolvenzrecht -- Ausländisches Recht, Rechtsvergleichung